Iraq : the day after - Pickering, Thomas Reeve, 1931-; Schlesinger, James R.; Schwartz, Eric (Council on Foreign Relations, 2003)
Report, issued on March 12, 2003, presenting recommendations on U.S. policy towards Iraq.